2023
DOI: 10.1186/s12951-023-02130-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosome, the glass slipper for Cinderella of cancer—bladder cancer?

Yuanyuan Yang,
Lintao Miao,
Yuchao Lu
et al.

Abstract: Exosomes are lipid bilayer vesicles with a diameter of 40–100 nm secreted by almost all cells. They have been found play crucial regulatory roles in various diseases. With the development of exosomes engineering technology, exosome-based drug delivery has also rapidly evolved. Bladder cancer is a worldwide disease with high morbidity and recurrence but lack of funding, so it is also called Cinderella. Some explorations have demonstrated that exosomes are important in the development, prognosis, diagnosis and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 215 publications
0
5
0
Order By: Relevance
“…Thus, liquid biopsy using exosomes may be more advantageous than liquid biopsy using ctDNA/cfDNA. Because tumor cell-derived exosomes contain the contents of parental cells, many studies have evaluated exosomes in serum to improve our understanding of the state of primary and metastatic tumor tissue [ 32 , 33 , 65 , 66 , 67 ]. In our study, we showed that serum exosomal BCYRN1 expression was significantly higher in patients with BC than in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, liquid biopsy using exosomes may be more advantageous than liquid biopsy using ctDNA/cfDNA. Because tumor cell-derived exosomes contain the contents of parental cells, many studies have evaluated exosomes in serum to improve our understanding of the state of primary and metastatic tumor tissue [ 32 , 33 , 65 , 66 , 67 ]. In our study, we showed that serum exosomal BCYRN1 expression was significantly higher in patients with BC than in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although several comparative methods using GAPDH have been reported, it is not yet the standard method for quantifying RNA in serum exosomes. Exosomes have also attracted attention as drug-transport mediators because of their affinity to cell membranes, owing to their dual lipid membrane structure [ 65 , 68 , 69 ]. For example, exosomes derived from BC cells have been shown to exhaust CD8+ cells and M2 macrophages in the tumor microenvironment to affect the antitumor immunity of the host [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of CCP is implicated in various diseases, including cancer [ 12 14 ]. Aberrations in genes governing CCP and apoptotic pathways contribute to tumorigenesis and progression [ 15 , 16 ]. Clinical and basic research has revealed CCP-related genes as prognostic indicators across cancer types [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported that noncoding RNAs has potential to prognosis bladder cancer as biomarker, such as CircRNAs, LncRNAs and MiRNAs 6 . Additionally, a novel biomarker of bladder cancer has been found is exosome, numerous studies investigating the association between exosomes and bladder cancer have identified the presence of exosome MALAT1, PCAT-1, and PTENP1 7 .…”
Section: Introductionmentioning
confidence: 99%